Multimodal integration of spontaneously produced representational co-speech gestures: an fMRI study. Issue 2 (7th February 2017) - Weisberg, Jill; Hubbard, Amy Lynn; Emmorey, Karen
ABSTRACT: To examine whether more ecologically valid co-speech gesture stimuli elicit brain responses consistent with those found by studies that relied on scripted stimuli, we presented participants with spontaneously produced, meaningful co-speech gesture during fMRI scanning ( n = 28). Speech presented with gesture (vs. either presented alone) elicited heightened activity in bilateral posterior superior temporal, premotor, and inferior frontal regions. Within left temporal and premotor, but not inferior frontal regions, we identified small clusters with superadditive responses, suggesting that these discrete regions support both sensory and semantic integration. In contrast, surrounding areas and the inferior frontal gyrus may support either sensory or semantic integration. Reduced activation for speech with gesture in language-related regions indicates allocation of fewer neural resources when meaningful gestures accompany speech. Sign language experience did not affect co-speech gesture activation. Overall, our results indicate that scripted stimuli have minimal confounding influences; however, they may miss subtle superadditive effects.